O41 'Everyone in': delivering hepatitis C treatment to vulnerable patients during the COVID-19 pandemic. (19th June 2022) - Chambers, Stacey; Unitt, Esther; Curtis, Bess
Abstract : Introduction: The Covid-19 pandemic severely disrupted healthcare services. In March 2020, the government announced the 'Everyone In' initiative to support everyone rough sleeping or in accommodation where they could not self-isolate, into safe, emergency accommodation. This presented an opportunity to offer treatment to a vulnerable cohort of individuals, known to be living with hepatitis C, who had previously not engaged with services to access treatment. Methods: From April to July 2020, the UHCW hepatitis team, in collaboration with members of the community drug and alcohol service, Change, Grow, Live (CGL), developed a virtual care pathway for service users known to be living with hepatitis C. Patients with a positive Hepatitis C RNA test, either by dried blood spot test or historic venous bloods were identified from CGL records. Service users were given mobile phones by CGL; patients were informed of their appointment by text and encouraged to keep their phones on. If necessary, multiple attempts at contact were made. Following an initial virtual assessment by the hepatitis CNS, treatment decisions were made at a remotely held hepatitis C MDT. Where genotypes were known, directly acting anti-viral agents (DAAs) were offered in accordance with the NHSE run rate card; others were offered pan-genotypic medication, with the prior agreement of the Operational Delivery Network (ODN) hub. Individuals who were previously rough sleeping or in accommodation where they could not self-isolate were provided with safe emergency accommodation through the 'Everyone In' government directive. Medication was delivered directly to the patients via a homecare delivery service. Regular contact and supportive texts from outreach workers and the hepatitis nurse encouraged compliance with medication. Upon relaxation of lock-down restrictions, patients were offered full physical examination and fibroscan, with referral into hepatology services if cirrhosis identified. Results: 26 CGL service users were identified as living with hepatitis C, of which 14 had previously failed to engage with our service. Between April 2020 and July 2020, we contacted all 26 patients for assessment and all 26 were commenced on DAAs. 3 patients were lost to follow up but 22/26 (85%) have had a confirmed sustained virological response (SVR). Once community clinics were reinstated, all patients were offered the opportunity for full clinical assessment with fibroscan. 9/26 (35%) patients attended for fibroscan and 2 were found to have evidence of cirrhosis. Both of these patients have subsequently engaged with hepatology follow up. Conclusions: With many services suspended for COVID-19, the Everyone In initiative afforded an opportunity to prioritise the hepatitis treatment of a vulnerable cohort of individuals. We have demonstrated a successful new pathway using telemedicine and home delivery of DAAs and shown that this can achieve high SVR rates in a population known to engage poorly with treatment services.